A study of the debris flow activity on the one-stepped channel slope - Sungduk KIM; Hojin LEE (Soil and Water Research, 2015)
The purpose of this study is to evaluate the behaviour and mechanism of debris flow on various slopes through numerical simulation. The numerical simulation was performed using the Finite Difference Element Method based on the equation of mass conservation and momentum conservation. In order to measure the behaviour of the debris flow, the debris flow of the straight rectangular channel slope and that of the one-stepped channel slope were compared. Firstly the water flow discharge, the water flow depth, and the sediment volume concentration at the slope downstream of the channel, depending on the different inflow water flow discharges at the upstream of the channel, were analyzed. The smaller the supply from the upstream of the channel, the water flow discharge and the water flow depth surged only at the point after the debris flow reached the downstream of the channel, and showed a tendency to decrease thereon after. On the other hand, when the supply at the upstream of the channel increased, the curve of the water flow discharge and the water flow depth was unsteadily high. Through the Root Mean Square ratio (RMS) comparison, the water flow discharge and water flow depth of the one-stepped channel slope was lower than that of the straight rectangular channel slope. Secondly, the water flow discharge, water flow depth, and sediment volume concentration depending on the change in the slope of the one-stepped channel slope were analyzed. The larger the slope, the larger the fluctuation in amplitude of the curve and this resulted in a higher water flow discharge distribution as well as in a wider fluctuation bandwidth. In the results of the study at each point, in the case of the straight rectangular channel, the water flow discharge and depth increased as it went downstream. This is because more erosion than deposition occurs when debris flow occurs at the upstream of the channel.